Impact of post‐operative serum albumin level on anastomotic leakage after transthoracic oesophagectomy for oesophageal squamous cell carcinoma. Issue 1 (5th November 2020) - Zhuge, Lingdun; Zheng, Difan; Mao, Hengyu; Xiang, Jiaqing; Chen, Haiquan
Abstract : In this study, we reported that serum albumin level on the first post‐operative day was an independent predictor for the occurrence of anastomotic leakage (AL) in patients with oesophageal squamous cell carcinoma who underwent transthoracic oesophagectomy. Patients with low album level post‐operatively were at higher risk of developing with AL. Increase of albumin level to the normal range post‐operatively could reduce the risk of AL. Abstract: Background: The correlation of post‐operative serum albumin level with the occurrence of anastomotic leakage (AL) in oesophageal squamous cell carcinoma (ESCC) remains unclear. The aim of this study was to evaluate the impact of post‐operative serum albumin level on AL after transthoracic oesophagectomy. Methods: Patients with ESCC who underwent transthoracic oesophagectomy between 2013 and 2017 in Fudan University Shanghai Cancer Center were included. The correlation of post‐operative serum albumin level with the occurrence and short‐term outcomes of AL was analysed. Results: Patients with serum albumin level of <35 g/L on the first post‐operative day were identified with higher frequency of AL in the whole study population (10.3% versus 6.1%; P < 0.001), intrathoracic anastomosis subgroup (7.1% versus 3.9%; P = 0.002) and cervical anastomosis subgroup (24.1% versus 16.0%; P = 0.042). Multivariate analysis showed that low albumin level was an independent risk factor of AL in the overall population (odds ratio (OR) 1.842; P < 0.001), intrathoracic anastomosis subgroup (OR 1.815; P = 0.006) and cervical anastomosis subgroup (OR 1.946; P = 0.013). In patients with AL, low albumin level was associated with poorer short‐term outcomes. For patients with low albumin level on the first post‐operative day, the probability of AL was significantly reduced if the level in the first post‐operative week was improved to the normal range (5.9% versus 14.9%; P < 0.001). Conclusion: Serum albumin level on the first post‐operative day was an independent predictor of AL in patients with ESCC receiving transthoracic oesophagectomy. Increase of albumin level to the normal range post‐operatively could reduce the risk of AL.